(untitled) (Quinto Sol, 2013)
In this article, I maintain that the official recognition of Rankülche identity reproduces, in the new pluralist framework of provincial identity, patterns of (in)visibilization analogous to those that decreed the vanishing of this in indigenous identity and group in the past. Such (in)visibilization is also identified in self-fashioned Rankülche strategies of identity, although they open up interstitial practices of freedom that endeavor to reappropriate official strategies of pluralist recognition. I investigate these problems in the dispositive of the Vanishing of the Ranquel, beginning in the 19th century, and the dispositive of the Return of the Rankülche started in the 1990s. The aim is twofold. On one hand, to detect the “phantoms” that would undermine in the past the inscription of the Ranquel as an Indian identity and that today haunt the representation of the Rankülche as a returning identity. On the other hand, I point to the ways in which those representational failures herald spaces where to develop practices of freedom that build up the cultural and political autonomy of the Indians in La Pampa.